2018
DOI: 10.1111/rda.13183
|View full text |Cite
|
Sign up to set email alerts
|

Influence of organic phosphorus on reproductive performance and metabolic profiles of anoestrous Farafra ewes in subtropics at the end of breeding season

Abstract: The effect of organic phosphorus on metabolic, haematological and hormonal status, restoration of ovarian functions and conception rate in anoestrous Farafra ewes in subtropics were evaluated. Anoestrous Farafra ewes (n = 24; 34.72 ± 0.52 kg body weight) were allocated into two equal groups: control and phosphorus groups. The ewes of phosphorus group were treated with sodium 4-dimethylamino-2-methyl-phenyl-phosphonate as an organic bound phosphorous twice a week for successive 3 weeks. Ovarian follicle develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Several strategies were suggested to alleviate the negative impacts of the transition period in small ruminant animals including diet formulation and additives (Hussein et al, 2015;Ali et al, 2021;Al-Mufarji and Mohammed, 2022;Al-Mufarji et al, 2022). Because of the negative influences of increased protein and urea in the diets on animals' fertility and health (McEvoy et al, 1997;Dawuda et al, 2002;Mohammed and Attaai, 2011; and the high cost of diets, it is important to search for useful supplements for productive and reproductive purposes (Senosy et al, 2017(Senosy et al, , 2018Cherif et al, 2018;Mohammed, 2022). It has been observed that there is an increasing interest in the use of M. oleifera as feed supplements for ruminant animals (Al-Mufarji and Mohammed, 2022;Al-Masruri et al, 2022).…”
Section: Advances Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Several strategies were suggested to alleviate the negative impacts of the transition period in small ruminant animals including diet formulation and additives (Hussein et al, 2015;Ali et al, 2021;Al-Mufarji and Mohammed, 2022;Al-Mufarji et al, 2022). Because of the negative influences of increased protein and urea in the diets on animals' fertility and health (McEvoy et al, 1997;Dawuda et al, 2002;Mohammed and Attaai, 2011; and the high cost of diets, it is important to search for useful supplements for productive and reproductive purposes (Senosy et al, 2017(Senosy et al, , 2018Cherif et al, 2018;Mohammed, 2022). It has been observed that there is an increasing interest in the use of M. oleifera as feed supplements for ruminant animals (Al-Mufarji and Mohammed, 2022;Al-Masruri et al, 2022).…”
Section: Advances Inmentioning
confidence: 99%
“…ovarian follicles were categorized into small (2-2.9 mm), medium (3-4.9 mm), and large-sized follicles (≥ 5 mm). The numbers of CL were counted and the diameters were measured (Senosy et al, 2017(Senosy et al, , 2018.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Stimulation of ovarian activity or treatment of dysfunctions was widely investigated through nutritional levels and ingredients (Nagasawa et al, 1989;Downing et al, 1995;Mohammed et al, 2005;Mohammed and Attaai, 2011;Gifre et al, 2017;Senosy et al, 2017Senosy et al, , 2018Mohammed, 2019;Mohammed et al, 2012Mohammed et al, , 2021Mohammed and Farghaly, 2018;Mohammed and Al-Hozab, 2020;Ali et al, 2021), hormonal supplementation (Zarazaga et al, 1996;, both hormonal and nutritional supplementation (Mohammed and Attaai, 2011). Because of the negative effects of increased energy and protein in the diet for humans and animals on health and fertility (McEvoy et al, 1997;Dawuda et al, 2002;Mohammed et al, 2012) and the high cost of diet, microalgae and their purified extracts were given in small quantity as replacers of hormonal stimulation.…”
Section: Reproductive Activitymentioning
confidence: 99%
“…Supplementing Se increased plasma concentrations of P 4 during late gestation in Holstein heifers (Kamada et al., 2014). Similarly, a significant increase in P 4 concentrations was reported in heat‐stressed sheep receiving a mineral supplement enriched with phosphorus (Senosy et al., 2018). Such a favourable effect of phosphorus could be attributed to its function in the phospholipids of the plasma membrane of luteal cells and its role in the synthesis of cyclic AMP in these cells.…”
Section: Discussionmentioning
confidence: 66%